Mewujudkan generasi literat nelalui perpustakaan perguruan tinggi (Tantangan UIN Imam Bonjol Padang Menghadapi HOAX) - Dian Hasfera (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
Hoax is a news or statement that has invalid information or fake that does not have a certainty that is deliberately spread out to make the situation becomes excited and cause fear. HOAX maked many reactions in society, debates among peers, even family conflicts, even RASIS with disagreed parties. This paper is a literature review, will further discuss how the role of the library as one of the information institutions and become a language partner in this case is UIN Imam Bonjol Padang embodies the students who become literary generation. UIN Imam Bonjol Padang Library can implement the following activities: Smooth information, user education, library instruction, bibliographic instruction, information competence, information skills, and information skill development. Then the student is also expected to have knowledge of hitches or HOAX news through the following stages: Consider the source, Read beyond the headline, Check the author, What is the support ?, check the date, is this some kind of joke ?, check your bias, and Consult with experts.